Antiviral mechanisms and preclinical evaluation of amantadine analogs that continue to inhibit influenza A viruses with M2S31N-based drug resistance - Tietjen, Ian; Kwan, Daniel C.; Petrich, Annett; Zell, Roland; Antoniadou, Theodosia; Gavriilidou, Agni Faviola Mika; Tzitzoglaki, Christina; Rallis, Michail; Fedida, David; Sureda, Francesc X.; Mestdagh, Cato; Naesens, Lieve; et al. (Antiviral research, 2025)
To better manage seasonal and pandemic influenza infections, new drugs are needed with enhanced activity against amantadine- and rimantadine-resistant…
Im Titel ist "S31N" hochgestellt
Online veröffentlicht: 11. Februar 2025, Artikelversion 17. Februar 2025
Gesehen am 11.11.2025